A Review of Dialectical Behavior Therapy - Ahmadi, Aazi; Gerthe, Jessica (Journal of Advanced Psychology, 2025)
Purpose: This review examines Dialectical Behavior Therapy (DBT), developed by Marsha M. Linehan, focusing on its theoretical foundations, treatment components, empirical efficacy, and adaptations for diverse clinical populations and settings. Methodology: A synthesis of empirical studies, meta-analyses, and clinical manuals was conducted to evaluate DBT and its adaptations, including DBT for Adolescents (DBT-A) and DBT Skills Training for Emotional Problem Solving for Adolescents (DBT STEPS-A). Findings: DBT is effective for borderline personality disorder, suicidality, eating disorders, depression, anxiety, and substance use across adolescents and adults. DBT-A reduces self-harm and suicidal ideation, particularly with family involvement, while DBT-STEPS-A shows promise in school settings. However, research gaps remain in cultural adaptations, social justice practices, and cost-effective delivery models. Unique Contribution to Theory, Practice, and Policy: The review highlights the need for culturally responsive DBT protocols, school-based and telehealth delivery, and policies supporting equitable access. Future research should examine culturally adapted interventions, evaluate cost-effectiveness, and compare DBT with other evidence-based treatments to enhance its global relevance and impact.